Pelatihan Pemanfaatan Data E-Puskesmas dalam Optimalisasi Perencanaan Layanan Kesehatan di Puskesmas Kendalkerep - Reni Yuli Astutik; Atik Setiawan Wahyuningsih; Fita Fitarusdian (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2026)
Digital transformation in the health sector requires improved data utilization, particularly at the level of primary care services. Community health centers, as the frontline of health service delivery, face challenges such as uneven digital literacy among health workers, inadequate infrastructure, and a weak culture of data-driven decision-making. A training program on the use of e-Puskesmas data was conducted at Puskesmas Kendalkerep to strengthen the capacity of health workers in integrating data into service planning processes. This study employed a quasi-experimental one-group pretest–posttest design involving 52 participants selected through total sampling. Data were collected through pretest–posttest assessments, observations, and a questionnaire based on six dimensions of planning optimization: data utilization, program effectiveness, decision-making quality, coordination and collaboration, monitoring and evaluation, and human resource and infrastructure capacity. The analysis revealed significant improvements across all dimensions after the training. The average pretest scores, which ranged from 45.50 to 57.50, increased to 82.50–92.50 in the posttest. The paired sample t-test produced t-values of 6.04–9.44, exceeding the critical value of 2.01 (p < 0.05), indicating a statistically significant difference before and after the training. Cohen’s d values ranged from 0.81 to 1.58, indicating large effect sizes, with the strongest impact observed in the dimension of coordination and collaboration. Observational findings also showed enhanced technical data-entry skills, greater participation in discussions, and increased awareness of the importance of data-driven planning.